Pengaruh Keselamatan dan Kesehatan Kerja, Komitmen Organisasi, dan Pengalaman Kerja terhadap Produktivitas Kerja PT Rayung Pelangi Nusantara Purbalingga - Nadila Herawati; Hima Barima (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This research is motivated by the declining level of work productivity of PT Rayung Pelangi Nusantara Purbalingga employees, which is suspected to be caused by the suboptimal implementation of occupational safety and health (K3), low organizational commitment, and less than optimal utilization of work experience. The main focus of this study is to analyze the influence of occupational safety and health (K3), organizational commitment, and work experience on employee work productivity partially. This study applies a quantitative approach through the application of multiple linear regression techniques with the help of SPSS version 25 software. The number of research samples consisted of 57 respondents selected using a purposive sampling method, while the data was obtained through a questionnaire instrument. The data analysis process involved validity tests, reliability tests, descriptive analysis, classical assumption tests, t tests, F tests, and coefficients of determination (R-Square). The research findings show that occupational safety and health (K3) has a positive and significant effect on work productivity, organizational commitment has a positive but not significant effect, and work experience has a negative and not significant effect. The coefficient of determination of 0.308 indicates that 30.8% of the variation in work productivity can be explained by these variables, while the remaining 69.2% is influenced by other factors not identified in this study. In conclusion, the increase in employee work productivity is more influenced by the implementation of good OHS, while organizational commitment and work experience have not shown a significant contribution. Therefore, companies are advised to strengthen the occupational safety and health (OHS) system and evaluate HR development strategies so that organizational commitment and work experience can have a greater impact on productivity.